Building a Corporate Culture Centered on Environment, Social, and Governance Principles in Indonesian Companies - Indra Ardiyanto; Luh Shinta Pratiwi; Mohammad Rifaldo Fajri; Yoga Firgiawan (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The rising global emphasis on Environmental, Social, and Governance (ESG) principles, driven by regulatory pressure, stakeholder expectations, and strategic demands for long-term resilience, has made the internal integration of ESG values into corporate culture an urgent priority for organizations, including those in Indonesia. This study examines how companies in Indonesia build a corporate culture based on environmental, social, and governance principles. The main goal is to explore the process of aligning these principles with the company vision and mission, identify integration challenges, and assess impacts on employee and organizational performance. A qualitative approach with multiple case studies was used in two Indonesian firms, one multinational and one local. Data came from in-depth interviews, document reviews, and observations. Findings show that strong top leadership commitment and a mindset shift are essential to make these principles part of the core business strategy. Key practices include renewable energy investments, vehicle fleet changes to electric, employee health programs, and community water projects. Challenges involve limited regulations and low understanding among business owners. Positive outcomes include higher employee engagement, productivity, and appeal to younger talent. Successful integration turns these principles into organizational identity, creating shared value and competitive advantage through authentic daily practices.